2018
DOI: 10.1096/fj.201801163r
|View full text |Cite|
|
Sign up to set email alerts
|

Decreased LIN28B in preeclampsia impairs human trophoblast differentiation and migration

Abstract: Preeclampsia (PE) is a common cause of maternal morbidity, characterized by impaired trophoblast invasion and spiral artery transformation resulting in progressive uteroplacental hypoxia. Given the primary role of LIN28A and LIN28B in modulating cell metabolism, differentiation, and invasion, we hypothesized that LIN28A and/or LIN28B regulates trophoblast differentiation and invasion, and that its dysregulation may contribute to PE. Here we show that LIN28B is expressed ∼1300‐fold higher than LIN28A in human t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
62
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 54 publications
(65 citation statements)
references
References 71 publications
3
62
0
Order By: Relevance
“…To avoid the spontaneous differentiation of PHTs, in this study, we used undifferentiated iPSCs and found that 24 hours exposure to hypoxia (1% oxygen) significantly decreased the expression of numerous C19MC miRNAs and several reprogramming factors including OCT4 and LIN28B, whereas the expression of EMT related genes was increased. The repression of LIN28B expression in iPSCs by hypoxia agrees with our previous study that showed that hypoxia decreased the expression of LIN28B in choriocarcinoma BeWo and JEG3 cells, and in placentas from preeclampsia-affected pregnancies 40 . In addition, repression of OCT4 induces loss of pluripotency and differentiation of ESC cells derived from the inner cell mass toward the trophectoderm lineage 41 .…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…To avoid the spontaneous differentiation of PHTs, in this study, we used undifferentiated iPSCs and found that 24 hours exposure to hypoxia (1% oxygen) significantly decreased the expression of numerous C19MC miRNAs and several reprogramming factors including OCT4 and LIN28B, whereas the expression of EMT related genes was increased. The repression of LIN28B expression in iPSCs by hypoxia agrees with our previous study that showed that hypoxia decreased the expression of LIN28B in choriocarcinoma BeWo and JEG3 cells, and in placentas from preeclampsia-affected pregnancies 40 . In addition, repression of OCT4 induces loss of pluripotency and differentiation of ESC cells derived from the inner cell mass toward the trophectoderm lineage 41 .…”
Section: Discussionsupporting
confidence: 91%
“…Immunohistochemistry. Cytokeratin and vimentin immunostaining of early human placental sections was performed as previously described 40,53 . Briefly, paraffin embedded sections were deparaffinized in xylene and rehydrated in a series of graded alcohol washes followed by antigen retrieval by boiling in citric acid (pH6.0).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Because then, we found that LIN28B in fact is the predominant LIN28 homolog expressed in human first‐trimester placenta, localized to the cytotrophoblast cells, and present in commonly used human trophoblast cell lines (West et al, ). This was also recently confirmed by Canfield et al (). Similar to LIN28B, AR is not present in the differentiated syncytiotrophoblast layer, which is positive for hCG, but appears to localize to trophoblast cells right beneath the syncytiotrophoblast layer.…”
Section: Discussionsupporting
confidence: 81%
“…Contrary to mice, human trophoblast cells primarily express LIN28B (Canfield et al, 2018;West et al, 2018), and in this study we explored the possibility that androgen receptor (AR) is a potential target for LIN28B. AR localizes to villous stromal cells, cytotrophoblast, and syncytiotrophoblast in term placenta (Iwamura, Abrahamsson, Benning, Cockett, & di Sant'Agnese, 1994;Horie, Takakura, Imai, Liao, & Mori, 1992), and previous work in our lab suggests AR is involved in regulating placental angiogenesis through its interaction with VEGFA during pregnancy (Cleys et al, 2014).…”
Section: Introductionmentioning
confidence: 99%